Fostering Transferable Creativity: A Core Role for Art Education in School Curriculum - Cropley, Arthur (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
Arts education occupies a fringe position in school curricula because the arts are widely regarded as accessible to only a chosen few and of little practical use, or as purely recreational. What is needed is understanding of the potential contribution of arts education to other areas of curriculum, including those often seen as the real core of school learning (“the three Rs”). The psychological processes and personal properties inherent to arts education correspond closely to those now regarded as vital right across the curriculum. In contrast, they are often neglected in conventional academic disciplines. Arts education is capable of promoting these processes and personal properties to transfer to other elements of the curriculum in the form of transferable creativity, but this will not occur without changes in mainline pedagogy, for example, in the assessment.